Impact of remineralized desalinated water on domestic services and hot water systems: experience at Adelaide Desalination Pilot Plant. Issue 1 (October 2013) - Reid, K.; Dixon, M. B.; Lasslett, S.; Pelekani, C.
Abstract : Membrane desalination technology is undergoing rapid expansion in Australia in response to drought and climate change. In preparation for the operation and maintenance of the 300 ML/day, Adelaide Desalination Plant (ADP), a pilot plant (ADPP), was constructed to evaluate several anticipated operational challenges. A main area of investigation was the control of downstream corrosion after remineralization. Desalinated water requires remineralization before distribution as its very low mineral content renders it highly corrosive. The impact of remineralized desalinated water on small scale, downstream infrastructure was investigated at the ADPP. Two domestic hot water systems (HWS) and a series of network pipe segments were fed with mains water and desalinated product water, and the effects on these assets was assessed. Differences in mains and desalinated water chemistry contributed to increased calcium carbonate scale formation in remineralized desalinated water fed HWS; however, calculations based on residential usage data revealed that this would not significantly impact upon the longevity of HWS operation. Pipe section testing in conjunction with computer modeling confirmed passivity of the remineralized desalinated water. Together, these results indicate that remineralization processes in place at the ADP are sufficient to produce a passive water supply, which will not detrimentally affect downstream infrastructure.